Cell line-dependent increase in cellular quercetin accumulation upon stress induced by valinomycin and lipopolysaccharide, but not by TNF-α. (November 2019) - Vissenaekens, Hanne; Grootaert, Charlotte; Rajkovic, Andreja; De Schutter, Kristof; Raes, Katleen; Smagghe, Guy; Van de Wiele, Tom; Van Camp, John
Abstract: As the interface between the luminal and internal environment, the intestinal epithelium is strongly exposed to food-related, host-related and microbial stress. Furthermore, the endothelial stress response plays an important role in vascular disease development, which may be improved upon consumption of dietary bioactives such as polyphenols. The impact of the latter, however, is largely individual-dependent and effects are, in most cases, only observed under mild diseased conditions. Here, it is hypothesized that the individual's stressor levels may contribute to this variable response. To this end, the impact of the stressors (i) valinomycin (as model for cereulide, food-related microbial metabolite), (ii) TNF-α (host-related) and (iii) lipopolysaccharide (gram-negative bacterial cell related) on flavonoid accumulation was investigated in several intestinal and endothelial cell lines. Flow cytometry, confocal microscopy and an in-house developed, robust and high-throughput spectrofluorometric method, showed that quercetin accumulated in all tested cell lines in a dose-dependent manner. Upon stress induced by valinomycin and to a lesser extent by lipopolysaccharide, but not by TNF-α, an increased quercetin accumulation was observed in proliferating intestinal and endothelial cells and not in differentiated intestinal or quiescent endothelial cells. Therefore, flavonoid accumulation may be a potential cellular stress response mechanism which strongly depends on the applied stressor, flavonoid, cell line and even growth conditions. This opens perspectives for further understanding the mechanisms by which cellular stress may shape the individual's response to bioactive compounds. Graphical abstract: Unlabelled Image Highlights: A novel spectrofluorometric method was developed. Quercetin accumulates in gut (Caco-2, HCT116) and endothelial (EA.hy926) cells. Valinomycin increased quercetin accumulation specifically in proliferating cells. LPS increased quercetin accumulation in proliferating Caco-2 cells. TNF-α did not significantly increase flavonoid accumulation.